2022
DOI: 10.1080/21655979.2022.2084253
|View full text |Cite
|
Sign up to set email alerts
|

Based on network pharmacology and in vitro experiments to prove the effective inhibition of myocardial fibrosis by Buyang Huanwu decoction

Abstract: Among cardiovascular diseases, myocardial fibrosis (MF) is a major pathological change underlying heart failure and is associated with a high mortality rate. However, the molecular mechanism underlying MF has remained elusive. Buyang Huanwu decoction (BYHWD), a traditional Chinese medicine (TCM) formula for cardiovascular diseases, exhibits good anti-inflammatory and blood-activating properties. In the present study, we studied the MF inhibitory effect of BYHWD using network pharmacology and experimental valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…The importance of medicinal plants in the search of drugs is well established today [ 5 7 ]. Some illustrative anticancer molecules include vinblastine, vincristine, paclitaxel, or camptothecin [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of medicinal plants in the search of drugs is well established today [ 5 7 ]. Some illustrative anticancer molecules include vinblastine, vincristine, paclitaxel, or camptothecin [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exploitation of medicinal plants traditionally used under rigorously well-conducted scientific investigations in vitro, in vivo, or in silico, has contributed significantly to the improvement of human health, with many pharmaceuticals deriving from botanicals [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Common targets for AM&AS and SCI were imported into STRING database ( https://cn.string-db.org/ ) [ 16 ]. As long as the species is limited to “Homo sapiens,” the confidence score is greater than 0.90.…”
Section: Methodsmentioning
confidence: 99%
“…The active pocket of puerarin was docked to the core target to determine the binding energy. Negative binding energy is typically thought to have critical potential, with values less than −5 kcal/mol thought to be more likely to bind ( Wang et al, 2022 ). The molecular docking results showed that puerarin had good binding energy for cAMP/PKA/CREB/c-Fos ( Table 3 and Figures 12A–D ).…”
Section: Resultsmentioning
confidence: 99%